Molecular Imaging-guided Precise Theranostics - WANG Guochang; ZHU Zhaohui (Xiehe Yixue Zazhi, 2022)
In recent years, molecular imaging and precise theranostics have appeared frequently in the Top 10 international hot frontiers in the field of clinical medicine, including accurate diagnosis and therapy of prostate cancer targeting prostate specific membrane antigen (PSMA). Molecular imaging-guided theranostics is a rapidly developing field, which is feasible to find one or more molecular probes for any disease-specific target to observe the in vivo expression and dynamic changes through molecular imaging.The molecular imaging can be applied to accurate diagnosis of diseases, guiding precise therapeutic radionuclide therapy, targeted drugs, and optical imaging-guided surgery. Therefore, it has a great prospect of clinical application and deserves a close attention by the majority of medical researchers and professionals.